Professional students’ technology readiness, prior computing experience and acceptance of an e-learning system / Lai Ming Ling and Chong Moi Moi - Lai, Ming Ling (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
This study examines professional students’ state of technology readiness, prior computing experience and acceptance of an e-learning system. We administered 2,189 questionnaires on students pursuing the professional examinations in Malaysia. A total of 453 usable questionnaires were received. Rockbridge Associates Inc (1999), the survey found that professional accounting students were neither highly techno-ready nor highly technoresistant. The respondents were classified into five categories, explorers (9%), pioneers (35%), skeptics (39%), paranoids (14%) and technology laggards (3%). Overall, the findings showed that the respondents had strong usage intentions of e-learning system; they exhibited positive attitudes towards elearning, and perceived that e-learning system was easy to use and was useful in enhancing their academic performance. This study provides the insight that professional bodies ought to intensify information and communication technologies (ICT) integration into the accounting education curriculum and assessment policies, and to motivate professional students in using ICT and e-learning.